PELAKSANAAN PROGRAM DESA MAJU INDRAGIRI HILIR JAYA PLUS TERINTEGRASI OLEH PEMERINTAH DESA PENGALIHAN KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 2023 - Safitri, Anisa Nur; ., Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study discusses the implementation of the Desa Maju Indragiri Hilir Jaya (DMIJ) Plus Terintegrasi Program by the Village Government of Pengalihan, Keritang District, Indragiri Hilir Regency in 2023. Despite ongoing issues related to both physical and non-physical development in Pengalihan Village, a significant portion of the DMIJ Plus Terintegrated Program's budget in 2023 was allocated to village governance activities. As a result, community involvement in the program's activities remained limited. The aim of this research is to examine the implementation of the DMIJ Plus Terintegrated Program by the Village Government of Pengalihan in 2023 and to identify the influencing factors. This study employs a qualitative approach with descriptive analysis. The data used consist of primary data collected through interviews with informants, and secondary data obtained from relevant documents. Data collection techniques include interviews and documentation. The research applies David C. Korten’s program implementation theory, which emphasizes three main elements: program appropriateness, implementing organization, and target group (beneficiaries). The findings reveal that the program was primarily focused on the operational aspects of village governance, while physical development and community empowerment remained limited due to budget constraints. Organizationally, the structure was in place, but the quality of human resources was still low. From the target group perspective, community participation was lacking due to limited understanding and direct involvement. Overall, the program implementation has not been optimal and has yet to fully address the community's needs. A more participatory approach, enhanced capacity of village apparatus, and strengthened budget management are necessary to ensure more effective and sustainable program implementation. Keywords: DMIJ Plus Terintegrated, Program, Village Government